Scleral Thinning Documented by Ultrasound Biomicroscopy after Plaque Therapy for Anterior Ciliary Melanoma. (19th May 2018) - Kuzmanović Elabjer, B.; Bušić, M.; Miletić, D.; Bjeloš, M.; Vukojević, N.; Bosnar, D.
ABSTRACT: Purpose : To evaluate, by ultrasound biomicroscopy (UBM), changes in scleral thickness after ruthenium-106 CCB and CCC plaque (Eckert & Ziegler BE-BIG GmbH, Berlin, Germany) therapy for anterior ciliary melanoma. Methods : Eleven patients with anterior ciliary melanoma underwent ruthenium-106 CCB and CCC plaque radiation with a radiation dose at the tumor apex of 80–100 Gy. UBM measurements performed prior to and after treatment were as follows: the largest prominence of the tumor perpendicular to the sclera and scleral thickness at scleral spur, 1.0 mm, and 2.0 mm posteriorly. Results : The article presents one year follow-up results for each of the 11 patients. The mean regression of the tumor of 24.3±9.31% was observed. The thinning of the sclera was statistically significant at the scleral spur (t=1.80, p ≤ 0.05) and at maximal tumor thickness (t=1.35, P =0.05). Conclusion : UBM documented significant thinning of the sclera at the scleral spur and overlying the maximal tumor thickness after Ru-106 CCB and CCC plaque radiation. Taking into consideration the shortcomings of the study—small sample size, insufficient probe resolution, and subjectively determined anatomic landmarks—observed minimal thickness change of the sclera does not necessarily mean its necrosis. However, thinning of the sclera documented at one year follow-up associated with very slow regression of the tumor indicates the need for the introduction of the CIA plaque treatment in our patients with anterior ciliary melanoma.